Effects of Emmersion in Boiling Water on Stress- Strain Test for Novolac Composite - Mahmood, H. S.; Abdul- Majeed, A. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The study of Stress- Strain relation for novolac reinforced by qujurate plant was carried out before and after the immersing in boiled water at 100C0 . It was found that the compression strength and surface hardness decreased when the composites immersed in boiled water for long times.